Analisis Alur Naskah Drama Nilam Binti Malin Karya Karta Kusumah - Sekar Wangi Arasti Yasmin; Wimbrayardi Wimbrayardi (Universitas Palangka Raya, 2024)
This study aims to analyze the plot of the drama script